Cross-border prevalence of putative-hypervirulent Klebsiella pneumoniae differs between tertiary hospitals in Austria and Germany - Bernd Neumann; Sophie Wilhelm; Jan Marco Kern; Joerg Steinmann (New Microbes and New Infections)
We conducted a prospective testing protocol for surveillance of putative hypervirulent Klebsiella pneumoniae in two tertiary hospitals in Germany and Austria, over a one year study period. In total, 45 (1.02 %) putative hvKp of around 4400 K. pneumoniae were identified. The study revealed a 3.3-times higher prevalence of putative hvKp in the German hospital.